"All Ears" – Learning (by) Listening (KULT_online, 2009)
Mechthild Hagen plumbs an insufficiently studied area of pedagogy with her investigation, Förderung des Hörens und Zuhörens in der Schule (Fostering Listening Skills in School). Revolving around learning listening and learning by listening, Hagen's thesis presents a practical model for promoting listening skills within a “cultural listening space”. The model and the results of its implementation at selected schools as part of the project “GanzOhrsein” (“All Ears”) clearly demonstrate the importance of expanding listening skills curricula, and include suggestions for achieving just this.